Venomous earth how arsenic caused the world's worst mass poisoning - Meharg, Andrew A. (Macmillan, 2005)
The compelling story of the worst chemical disaster in human history--unfolding now. It explores the geology, politics and biology of why tens of thousands of people are dying, hundreds of thousands are developing cancer and tens of millions are at risk, in Bangladesh, India, and beyond, from arsenic-contaminated well water. Andrew Meharg compares this scenario with that in other arsenic-rich zones of the world where drinking water is tainted, such as extensive areas of Southwestern USA, the Alto Plano of South America and New Zealand's volcanic regions. He details historical precedents spanning thousands of years in mining and smelting communities, caused by the widespread use of arsenic in alchemy, farming, medicine and manufacturing. His tale takes in William Morris, Paracelsus, George W. Bush, and a cosmetic that killed two popes.